The Role of Islamic Spirituality in Coping with Stress and Depression - Muhimmatul Hasanah (Faculty Ushuluddin, Adab and Dakwah UIN Palangka Raya, 2025)
The increasing prevalence of stress and depression in modern society poses a serious challenge to mental health, particularly amid the complexity of social pressure and rapid lifestyle changes. In this context, Islamic spirituality offers a coping dimension that is not only psychological but also transcendental, grounded in values of iman (faith), sabr (patience), shukr (gratitude), and tawakkal (trust in God). This study aims to examine the role of Islamic spirituality as an adaptive coping mechanism for stress and depression using a qualitative-descriptive approach. Data were collected through a literature review and in-depth interviews with individuals who regularly engage in spiritual practices such as dzikrullah (remembrance of God), night prayer (qiyam al-layl), and Qur’anic recitation. The findings reveal that Islamic spirituality significantly enhances self-acceptance, gratitude, and inner peace, thereby fostering emotional resilience and reducing psychological distress. These spiritual values help individuals reinterpret life’s pressures positively and maintain mental balance through faith-based awareness. The study further contributes to the development of Islamic Counseling Practice by providing an evidence-based framework for integrating spiritual coping techniques, such as dzikrullah, sabr, and tawakkal, into therapeutic interventions aimed at strengthening Muslim clients’ mental well-being.